Penerapan Model SBL (Simulation Based Learning) dalam Meningkatkan Aktivitas Belajar Siswa pada Pembelajaran IPA - Hanto Hanto; Yuniasih Yuniasih; Faizatul Khasanah; Parjono Parjono; Umi Zulaifah; Nurul Chotimah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Learning activity is an important factor in the success of the teaching and learning process, because it is a measure of the extent to which students can achieve the expected results. One of the learning models that can increase learning activities is SBL (Simulation Based Learning). This study aims to describe the steps, advantages, and disadvantages of applying the SBL model in science learning at MTs Negeri 1 Klaten, MAN 1 Kebumen, and MAN 2 Rembang. The research method used a qualitative approach with the subject of science teachers in the three schools, while data collection techniques were carried out through interviews, observation, and documentation. The results showed that the steps of implementing SBL included the selection of simulation topics, appointment of students as actors, preparation of scenarios with clear rules, explanation of activities and their consequences, trial procedures, implementation of simulations with teacher supervision, and reflective discussions after the activity. The advantages of SBL include developing creativity, fostering courage and self-confidence, enriching knowledge, attitudes, and social skills, increasing motivation, and helping understanding the material. However, the disadvantages are that the simulation experience does not always match reality, poor management can make it just entertainment, and psychological factors such as shyness and fear can hinder students. Thus, the SBL model is proven to be effective in increasing science learning activities.